Social Innovation Canada - SI Canada (Social Innovation Canada, 2022)
Social Innovation Canada will create a unique, inclusive and open movement to put people and planet first. It will provide the collaborative infrastructure to strengthen Canada’s social innovation ecosystem, empowering people, organizations and systems with the tools, knowledge, skills and connections that they need to solve real and complex problems. Initiative pancanadienne émergente visant à connecter les praticiens de l'innovation sociale, à renforcer les capacités de notre secteur et à élever ce travail au Canada et au-delà.